Response to first-line erlotinib in a false EGFR mutation-negative patient with non-small-cell lung cancer: Make no assumptions - Caixia Deng; Hu Luo; Xiangdong Zhou (Open Journal of Cell and Protein Science - Peertechz Publications, 2018)
So far, in the advanced non-small cell lung cancer (NSCLC) with clear epidermal growth factor receptor (EGFR) gene status, the treatment remmendations has reached an agreement: for patients with EGFR mutation-positive, epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) is the first choice, which can maximize the benefit from the treatment; while for the patients with wild-type EGFR gene, we should give priority to chemotherapy whether in the first-line or second-line therapy. However, about 70% of the patients were diagnosed at the late stage, so the pathological diagnosis and EGFR gene mutation detection depend on small specimens. Due to the limitations of small specimens, it may lead false EGFR mutation-negative, which results in these patients losing the opportunity to receive EGFR-TKI. Therefore, more simple and accessible predictors, in order to discover these potential false negatives of EGFR mutation, are urgently warranted. Here, we report a case showing a positive response to erlotinib treatment in the first-line setting. The patient, an middle-aged male smoker with stage IV NSCLC, had a tumor that was EGFR mutation-negative (wild-type EGFR). Based on this clinical case, we will discuss how to distinguish the false negatives of EGFR mutation and explore the predictors of EGFR mutation-positive , response and survival to EGFR-TKIs in first-line treatment.